2002
DOI: 10.2304/ciec.2002.3.2.11
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Pre-School Teachers' Thoughts about Computer-Assisted Instruction

Abstract: In this research, pre-school teachers' thoughts about computerassisted instruction, and the positions of pre-schools regarding the use of computers are studied. The sample of the study consisted of 22 managers and 111 pre-school teachers in 22 schools in Ankara, Turkey. A questionnaire was given to the teachers. A 'General Information Form' was also given to managers in order to determine the extent of the use of computers in pre-schools. Fisher chi-square and chi-square statistical techniques were used to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 5 publications
0
17
0
2
Order By: Relevance
“…However, the lack of uptake is evident in the schooling sector, where computer technology within the earlier years of schooling is seen as less important than in the upper years of schooling. Bayhan et al (2002) and Ertmer (2005) support Downes et al's (2001) claims that despite significant technology being accessible to teachers, there has been little uptake of these tools in education. Ertmer suggests that this is, in part, due to teachers' lack of pedagogical knowledge on how to use the tools effectively within the context of the learning environment.…”
Section: Technology In Early Childhood Settingsmentioning
confidence: 70%
See 1 more Smart Citation
“…However, the lack of uptake is evident in the schooling sector, where computer technology within the earlier years of schooling is seen as less important than in the upper years of schooling. Bayhan et al (2002) and Ertmer (2005) support Downes et al's (2001) claims that despite significant technology being accessible to teachers, there has been little uptake of these tools in education. Ertmer suggests that this is, in part, due to teachers' lack of pedagogical knowledge on how to use the tools effectively within the context of the learning environment.…”
Section: Technology In Early Childhood Settingsmentioning
confidence: 70%
“…Ertmer suggests that this is, in part, due to teachers' lack of pedagogical knowledge on how to use the tools effectively within the context of the learning environment. Bayhan et al (2002) reported that their participants felt that computers restricted the social development of children. Judge et al (2002) reported a similar position, arguing that there has been a rapid growth in the area of technology and teachers need to be supported in its uptake so as to ensure quality learning experiences for young students.…”
Section: Technology In Early Childhood Settingsmentioning
confidence: 99%
“…Bayhan et al explored the use of computers at home to develop mathematical ideas and reported that there were considerable potential for computer games to support such learning [29].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Also, there have been a substantial number of studies in Turkey about students and teachers' attitudes towards technology use (e.g. Akkoyunlu, 1996;Altun, 2003;Asan, 2002;Bayhan et al, 2002;Deniz, 2005;Gomleksiz, 2004), however, most of those studies examined the interaction between attitude toward technology and students ND teacher/prospective. For example, Altun (2003) studied the interaction between prospective teachers' attitude and students towards computers and their academic achievement, the study concluded that academic achievement could be considered as an effective contributor to participants' attitudes toward computers (Akpinar and Bayramoğlu, 2008).…”
Section: Importance Of It In Teaching and Learningmentioning
confidence: 99%